Plugging agent as well as preparation method and application thereof
By using leak plugging agents containing deformation pressure-bearing resin and temperature-resistant fibers in deep well crack reservoirs, the problem of insufficient gentle compressive resistance in the prior art is solved, efficient leak plugging and reservoir protection is achieved, the leakage plugging success rate is improved, and the reservoir permeability is restored during the oil production stage.
Patent Information
- Application Number
- CN202311079652.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-25
AI Technical Summary
The prior art is difficult to effectively solve the problem of vicious leakage in deep well crack reservoirs, especially in high temperature and high pressure environments. The gentle and compressive resistance of the leak-blocking material is insufficient, and it is difficult to effectively reside in the crack-blocking well wall, resulting in a low leakage-blocking success rate.
A leak plugging agent including water, a strong retention acid-soluble pressure-bearing gel, acid-soluble anti-temperature fiber and degradable deformation pressure-bearing resin is used to improve the retention and temperature resistance of the leak plugging liquid through a high-temperature degradable deformation pressure-bearing resin and anti-temperature fiber network to form a high-pressure deformation elastic solidified body.
When the crack opens, the deformation pressure-bearing resin is inserted into the reservoir pore seam. After high temperature expansion, the elastic pressure bearing capacity of the plugging skeleton is improved. In combination with the anti-temperature fiber, the plugging system is retained in time within 2.5 minutes, the expansion rate can reach more than 30%, and the sealing pressure bearing capacity reaches more than 29MPa, which improves the leakage plugging success rate of crack leakage, and restores the reservoir permeability through acid dissolution and high-temperature degradation during the oil production stage.
Smart Images

Figure BDA0004413866060000161 
Figure BDA0004413866060000162 
Figure BDA0004413866060000171
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of drilling fluid, and in particular relates to a plugging agent and a preparation method and application thereof. Background Art
[0002] Malignant leakage in fractures and karst formations leads to a large loss of drilling time, consumption of a large amount of plugging materials, and even major accidents such as stuck drill and blowout, resulting in significant economic losses and seriously restricting the progress of exploration and development. The problem of malignant leakage in fractures and karst formations is a difficult and hot issue in the current and future research of drilling projects, requiring the plugging working fluid to have strong retention and plugging capabilities, and certain resistance to temperature and pressure. As drilling deepens, the leakage of deep well fracture reservoirs has put forward higher requirements for plugging technology, further improving the comprehensive resistance to temperature and pressure of plugging materials, and adding more difficulties to reservoir protection.
[0003] For example, in the carbonate reservoirs of Block 10 of the Tahe Oilfield, there are various leakage spaces such as caves and cracks, showing serious heterogeneity. The fracture-cave system has a wide plane distribution and a large vertical span. Malignant leakage often occurs during drilling operations. While losing drilling fluid, it may also bring other complex situations, delay the construction period, and cause serious economic losses.
[0004] The current reservoir vicious leakage technology is mainly aimed at reservoir leakage below medium and high temperatures (150°C), and usually uses degradable or acid-soluble organic gel plugging technology or inorganic gel consolidation technology.
[0005] For example, Chinese patent CN 114058359B "Preparation method and application of degradation gel system for drilling and plugging of deep-water and ultra-deep-water fractured reservoirs" discloses a high-elasticity and low-viscosity efficient degradation gel system for drilling and plugging of fractured reservoirs, which can be applied to 60-110°C. It is prepared with 2.0-3.8% water-soluble polymer, 0.8-2.2% dynamic covalent borate bond crosslinker, 0.01-0.05% stabilizer and 0.07-0.8% hydrophilic fiber, forming a gel with adjustable gelation time, high gel strength and strong plugging ability, which can effectively prevent fracture leakage during drilling. The low-viscosity and high-elastic gel formed by the gel system has the advantages of strong retention, short gel breaking time, low viscosity of residual liquid after gel breaking, and little damage to fractured reservoirs, which can achieve the reservoir protection goal in the process of preventing leakage and plugging of fractured reservoirs during drilling. The maximum pressure bearing capacity of the fracture reservoir with a crack width of 0.5-3.2mm sealed at 80℃ can reach 7.2MPa.
[0006] For example, Chinese patent CN112442343B "A composite gel plugging agent and its preparation method" discloses the preparation of a high-viscosity, low-elastic composite gel plugging agent. The toughening agent is dispersed in water to obtain a toughening dispersion; the temperature-resistant and salt-resistant polymer is dispersed in the toughening dispersion to obtain a polymer dispersion; the cross-linking agent is added to the polymer dispersion, mixed evenly, and the composite gel plugging agent is obtained. The actual pressure resistance reaches 20MPa, the temperature resistance reaches 160℃, the stable period is greater than 30 days, and the gelling time is controllable at 4-10h.
[0007] The biggest advantage of these two gel reservoir protection technologies is their high acid solubility rate and optimal reservoir protection effect, which can reach 90-100%, but their heat and pressure resistance are poor. The temperature resistance of the gel can reach 140°C, but the continuous stability time of the gel at high temperature is short, which is easy to cause leakage, and the pressure resistance generally does not exceed 5-10MPa. If the uniaxial compressive strength test gel is used, the colloid compressive strength is even lower, not exceeding 1MPa; in addition, the cost is relatively high.
[0008] As a typical solidifying material, cement is cheap and has a high pressure-bearing capacity. It can produce high-strength plugging for large cracks and cave leaks, and is widely used for plugging leaks at the site of malignant leaks. Therefore, in the research and development of malignant leaks in reservoirs, cement is combined with acid-soluble materials to form a reservoir leak prevention and plugging technology.
[0009] For example, Chinese patent CN112210353B discloses "A high-loss and high-acid-soluble plugging agent for reservoir plugging and its preparation method", which includes: 1-2 parts of suspended reinforcing agent; 30-40 parts of gelling material; 35-45 parts of acid-soluble main material; 8-10 parts of filter aid enhancer; 8-15 parts of accelerating early strength agent. Under the joint action of various components of the present invention, the plugging agent obtained can quickly lose water on the one hand, with a loss time of about 25s, forming a tight sealing plugging layer; on the other hand, it can quickly solidify, shorten the plugging construction time, improve the drilling time, especially improve the pressure bearing capacity of fractured reservoirs, thereby ensuring the stability of the well wall during drilling. The plugging agent provided by the present invention has an acid solubility of more than 80%, and it is easy to acidify and unblock in the later oil production operation, thereby improving the recovery rate. The solidification strength tested by the YAW-300 pressure testing machine for 12 hours can reach 13.9MPa.
[0010] Although this inorganic solidified gel reservoir malignant leakage plugging agent uses cement cementitious materials with high pressure bearing capacity, the added amount is only 30-40%, and a large amount of acid-soluble main materials calcium carbonate and mica are mixed in the middle, and 16-25 parts of calcium oxide enhancer, calcium chloride and sodium sulfate early strength agent are added at the same time. These non-cementitious materials are filled between the cements, resulting in a significant decrease in the overall compressive strength of the cement gel system. When the mixed particles are added at a concentration of 190%, the compressive strength is lower than 1.5MPa, and the plugging slurry is severely thickened as a whole and difficult to pump; within the effective preparation concentration range, its uniaxial compressive strength is between 0.2-1.5MPa. In addition, this inorganic solidified cement gel has insufficient retention and is easy to flow along the well wall. It cannot effectively stay on the fractured well wall, resulting in low plugging success efficiency.
[0011] Therefore, there is an urgent need for a deformation-bearing pressure plugging agent for fractured reservoir leakage, which can effectively plug the malignant leakage reservoir when the fracture opens. During the oil production stage, it can open the formation seepage channel and restore the reservoir permeability through acid dissolution and high-temperature degradation. Summary of the invention
[0012] In order to solve the above problems in the prior art, the present invention provides a plugging agent and a preparation method and application thereof.
[0013] In the first aspect, the present invention provides a plugging agent, which comprises, by weight:
[0014] 100-250 parts of water, 150-300 parts of strong retention acid-soluble pressure-bearing gel, 0.5-5 parts of acid-soluble temperature-resistant fiber, and 2-20 parts of degradable deformation pressure-bearing resin.
[0015] As a specific embodiment of the present invention, the strong retention acid-soluble pressure-bearing gel includes, by weight: 0.5-1.5 parts of retention gel, 35-50 parts of gelling particles, 55-65 parts of acid-soluble particles, 10-25 parts of composite coagulant, 1-5 parts of fiber reinforcement, and 60-100 parts of compressive density regulator.
[0016] As a specific embodiment of the present invention, the retention gel is a calcium-resistant retention gel powder, which is selected from at least one of hydroxyethyl cellulose, hydroxyethyl methyl cellulose and hydroxypropyl methyl cellulose.
[0017] As a specific embodiment of the present invention, the acid-soluble particles include carbonate particles, preferably at least one of calcite, limestone, calcium carbonate and barium carbonate, and the particle size thereof is 3-15 um.
[0018] According to the present invention, the acid-soluble particles include carbonate particles, but calcium carbonate particles are generally selected from the perspective of cost and industrialization.
[0019] As a specific embodiment of the present invention, the gelling particles include at least one of G-grade silicate cement or sulphoaluminate cement for oilfield cementing.
[0020] As a specific embodiment of the present invention, the composite coagulant is selected from at least one of sodium silicate, calcium oxide, iron oxide or magnesium oxide.
[0021] As a specific embodiment of the present invention, the fiber reinforcement is selected from at least one of carbon fiber, high temperature resistant filling fiber PA66, aromatic polyamide fiber, and nano graphite fiber.
[0022] As a specific embodiment of the present invention, the compressive density regulator is selected from at least one of iron ore powder, barite, and quartz sand.
[0023] As a specific embodiment of the present invention, the acid-soluble temperature-resistant fiber is selected from at least one of sepiolite fiber and basalt fiber.
[0024] As a specific embodiment of the present invention, the degradable deformation pressure-bearing resin is selected from at least one of epoxy polymer shape memory resin, carbon fiber reinforced thermosetting resin-based composite material, and styrene-butadiene polymer.
[0025] As a preferred embodiment of the present invention, the degradable deformation pressure-bearing resin is selected from at least one of glycerol ether-type modified deformation pressure-bearing epoxy resin SMEP, carbon fiber reinforced thermosetting resin SA-DA, and acrylonitrile-butadiene-styrene ABS type resin PA-737.
[0026] As a preferred embodiment of the present invention, the degradable deformation-bearing pressure-bearing resin is a glycerol ether-type modified deformation-bearing pressure-bearing epoxy resin SMEP.
[0027] As a specific embodiment of the present invention, the preparation method of the glycerol ether type modified deformation pressure-bearing epoxy resin SMEP comprises:
[0028] A1: Evenly mix the water-based epoxy resin emulsion, the epoxy monomer polypropylene glycol diglycidyl ether, the curing agent diglycolamine and tetravinylpentamine, and heat and cure to obtain a first cured product;
[0029] A2: Evenly mix the waterborne epoxy resin emulsion, diaminodiphenyl sulfone and tetravinylpentamine, and heat until solidified to obtain a second solidified body;
[0030] A3: The first solidified body and the second solidified body are mixed and granulated to obtain a glycerol ether type modified deformation epoxy resin SMEP.
[0031] As a specific embodiment of the present invention, in the step A1, the mass ratio of the epoxy resin, the epoxy monomer polypropylene glycol diglycidyl ether, diglycolamine and tetravinylpentamine is 100:(5-15):(20-30):(2-8); preferably, the mass ratio is 100:10:25:5.
[0032] As a specific embodiment of the present invention, in the step A1, the curing temperature is 60-100°C, the curing time is 2-4h, and the glass transition temperature of the first cured body obtained by DSC measurement is 80°C.
[0033] As a specific embodiment of the present invention, in step A2, the mass ratio of the waterborne epoxy resin, diaminodiphenyl sulfone and tetravinylpentamine is 100:(50-70):(10-30); preferably, the mass ratio is 100:60:20.
[0034] As a specific embodiment of the present invention, in the step A2, the curing temperature is 80-140°C, and the curing time is 2-10h; preferably, curing at 80°C for 4h, curing at 120°C for 2h, and curing at 140°C for 2h, and the glass transition temperature of the obtained cured body A2 measured by DSC is 130°C.
[0035] As a specific embodiment of the present invention, in step A3, the mass ratio of the first solidified body to the second solidified body is (1-3):1; preferably, the mass ratio is 2:1.
[0036] In a second aspect, the present invention provides a method for preparing the plugging agent according to the first aspect, comprising the following steps:
[0037] S1: mixing gelling particles, acid-soluble particles, composite coagulant, fiber reinforcing agent, water, retention gel, and compression density regulator to obtain a strong retention acid-soluble pressure-bearing gel;
[0038] S2: Evenly mix the strong retention acid-soluble pressure-bearing gel obtained in step S1, the acid-soluble temperature-resistant fiber, and the degradable deformation-dependent pressure-bearing resin to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0039] As a specific embodiment of the present invention, in step S1, by mass fraction, the gelling particles are 35-50 parts, the acid-soluble particles are 55-65 parts, the composite coagulant is 10-25 parts, the fiber reinforcement is 1-5 parts, the retention gel is 0.5-1.5 parts, and the compressive density regulator is 60-100 parts.
[0040] As a specific implementation of the present invention, in the step S2, by mass fraction, 0.5-5 parts of acid-soluble temperature-resistant fiber and 2-20 parts of degradable deformation-bearing pressure-bearing resin are used.
[0041] As a specific embodiment of the present invention, the mixing conditions in step S1 and step S2 independently include: a stirring rate of 60000-110000 rpm, and a stirring time of 5-10 min.
[0042] In a third aspect, the present invention provides the use of the plugging agent described in the first aspect or the plugging agent prepared by the preparation method described in the second aspect in the field of deep well fractured reservoirs.
[0043] The above raw materials in the present invention can be prepared in-house or commercially available, and the present invention is not particularly limited thereto.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The plugging agent of the present invention aims at the problem of leakage in fractures or crack-hole type in high-temperature reservoirs of deep wells. It uses high-temperature degradable deformation pressure-bearing resin as the initial pressure-bearing bridging material, and cooperates with acid-soluble temperature-resistant fibers to form a network to improve the retention of the plugging liquid, intercept low-cost strong retention acid-soluble pressure-bearing gel, and form a high-pressure deformation elastic consolidation body with a temperature resistance of more than 200°C. Its characteristics, advantages and performance indicators are as follows:
[0046] 1. When the cracks open, the deformation pressure-bearing resin can be inserted into the reservoir pores and firmly bridge them. After high temperature, it will undergo phase change and expand, thereby improving the elastic pressure-bearing capacity of the plugging skeleton and, in combination with temperature-resistant fibers, timely intercepting the plugging liquid.
[0047] 2. Strong retention and acid-soluble pressure-bearing gel has the characteristics of strong retention, micro-expansion and acid-soluble. Under the interception of deformation pressure-bearing resin and fiber grid, it is quickly retained and accumulated, and efficiently fills the vicious leakage space. Its plugging system can be retained in time within 2.5 minutes.
[0048] 3. When gradually bearing pressure and plugging under high temperature and high pressure environment at the bottom of the well, the deformation pressure-bearing resin shows gelling properties and gradually strengthens, and the gelling particles gradually expand and consolidate under the action of the composite coagulant. The combination of the two firmly binds the plugging materials of different properties in the plugging system, forming an ultra-low permeability high-pressure plugging body with the well wall, thereby improving the success rate of fracture leakage plugging. The expansion rate of the plugging system can reach more than 30%, and the pressure-bearing capacity of plugging the leaking layer can reach more than 29MPa.
[0049] 4. In the oil production stage, acid dissolution can be used to block the seepage channels in the formation in the early stage. In the later stage, the deformation pressure-bearing resin is gradually degraded under high temperature, and some residual plugging materials resume the free flow state, thereby restoring the plugging layer from ultra-low permeability to high permeability and opening the oil and gas channel. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0051] The specific information of the reagents used in the embodiments of the present invention is as follows:
[0052] Basalt fiber, Taian Haosong Fiber Co., Ltd.;
[0053] High temperature resistant filling fiber, PA66 from BASF, Germany, Dongguan Yili Plastic Co., Ltd.;
[0054] Hydroxyethyl cellulose, HEC, Jiangsu Rayen Environmental Protection Technology Co., Ltd.;
[0055] Hydroxyethyl methylcellulose MHEC, Jinzhou Tujin Building Materials Co., Ltd.;
[0056] Carbon fiber reinforced thermosetting resin SA-DA.
[0057] Example 1
[0058] This embodiment provides a plugging agent and a preparation method thereof, the specific details of which are as follows:
[0059] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 35 parts of G-grade oil well cement, 57 parts of ultrafine calcium carbonate, 10 parts of sodium silicate, 3 parts of calcium oxide, and 0.5 parts of aramid fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 200 mL of clean water, and stir at 100,000 rpm for 10 min; then add 0.6 parts of retention gel hydroxyethyl methylcellulose, and stir at the same speed for 20 min; after being uniformly mixed, add 80 parts of barite, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0060] S2: Preparation of deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 2 parts of sepiolite fiber and 3 parts of acrylonitrile-butadiene-styrene (PA-737) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0061] Example 2
[0062] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 1, except that different amounts of compressive density are added to S1 for adjustment. The specific details are as follows:
[0063] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 35 parts of G-grade oil well cement, 57 parts of ultrafine calcium carbonate, 10 parts of sodium silicate, 3 parts of calcium oxide, and 0.5 parts of aramid fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 200 mL of clean water, and stir at 100,000 rpm for 10 min; then add 0.6 parts of retention gel hydroxyethyl methylcellulose, and stir at the same speed for 20 min; after being uniformly mixed, add 90 parts of barite, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0064] S2: Preparation of deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 2 parts of sepiolite fiber and 3 parts of acrylonitrile-butadiene-styrene (PA-737) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0065] Example 3
[0066] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Embodiment 1, except that different amounts of compressive density adjustment are added to S1, and different amounts of deformation pressure-bearing resin are added to S2. The specific details are as follows:
[0067] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 35 parts of G-grade oil well cement, 57 parts of ultrafine calcium carbonate, 10 parts of sodium silicate, 3 parts of calcium oxide, and 0.5 parts of aramid fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 200 mL of clean water, and stir at 100,000 rpm for 10 min; then add 0.6 parts of retention gel hydroxyethyl methylcellulose, and stir at the same speed for 20 min; after being uniformly mixed, add 90 parts of barite, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0068] S2: Preparation of deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 2 parts of sepiolite fiber and 5 parts of acrylonitrile-butadiene-styrene (PA-737) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0069] Example 4
[0070] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Embodiment 1, except that different composite coagulants and different amounts of compressive density are added to S1, and different amounts of deformation pressure-bearing resin are added to S2. The specific details are as follows:
[0071] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 35 parts of G-grade oil well cement, 57 parts of ultrafine calcium carbonate, 10 parts of sodium silicate, 2 parts of calcium oxide, 2 parts of iron oxide and 0.5 parts of aramid fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 200 mL of clean water, and stir at 100,000 rpm for 10 min; then add 0.6 parts of retention gel hydroxyethyl methylcellulose, and stir at the same speed for 20 min; after being uniformly mixed, add 90 parts of barite, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0072] S2: Preparation of deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 2 parts of sepiolite fiber and 5 parts of acrylonitrile-butadiene-styrene (PA-737) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0073] Example 5
[0074] This embodiment provides a plugging agent and a preparation method thereof, the specific details of which are as follows:
[0075] S1: Preparation of strong retention acid-soluble pressure-bearing gel: weigh 32 parts of G-grade oil well cement, 5 parts of sulphoaluminate cement, 55 parts of ultrafine calcium carbonate, 15 parts of sodium silicate, 5 parts of calcium oxide, and 1 part of nano-graphite fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 200 mL of clean water, and stir at 100,000 rpm for 10 min; then add 0.8 parts of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 80 parts of quartz sand, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0076] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 2 parts of basalt fiber and 5 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added into S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0077] Example 6
[0078] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 5, except that different amounts of compressive density are added to S1 for adjustment. The specific details are as follows:
[0079] S1: Preparation of strong retention acid-soluble pressure-bearing gel: weigh 32 parts of G-grade oil well cement, 5 parts of sulphoaluminate cement, 55 parts of ultrafine calcium carbonate, 15 parts of sodium silicate, 5 parts of calcium oxide, and 1 part of nano-graphite fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 200 mL of clean water, and stir at 100,000 rpm for 10 min; then add 0.8 parts of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniformly mixed, add 90 parts of quartz sand, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0080] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 2 parts of basalt fiber and 5 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added into S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0081] Example 7
[0082] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Embodiment 5, except that different amounts of compressive density adjustment are added to S1, and different amounts of deformation pressure-bearing resin are added to S2. The specific details are as follows:
[0083] S1: Preparation of strong retention acid-soluble pressure-bearing gel: weigh 32 parts of G-grade oil well cement, 5 parts of sulphoaluminate cement, 55 parts of ultrafine calcium carbonate, 15 parts of sodium silicate, 5 parts of calcium oxide, and 1 part of nano-graphite fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 200 mL of clean water, and stir at 100,000 rpm for 10 min; then add 0.8 parts of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniformly mixed, add 90 parts of quartz sand, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0084] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 2 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0085] Example 8
[0086] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Embodiment 1, except that different composite coagulants and different amounts of compressive density are added to S1, and different amounts of deformation pressure-bearing resin are added to S2. The specific details are as follows:
[0087] S1: Preparation of strong retention acid-soluble pressure-bearing gel: weigh 32 parts of G-grade oil well cement, 5 parts of sulphoaluminate cement, 55 parts of ultrafine calcium carbonate, 15 parts of sodium silicate, 5 parts of calcium oxide, 2 parts of iron oxide and 1 part of nano-graphite fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 200 mL of clean water, and stir at 100,000 rpm for 10 min; then add 0.8 parts of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 90 parts of quartz sand, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0088] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 2 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0089] Example 9
[0090] This embodiment provides a plugging agent and a preparation method thereof, the specific details of which are as follows:
[0091] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 70 parts of quartz sand and 4 parts of iron minerals, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0092] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0093] Example 10
[0094] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Embodiment 9, except that different amounts of compressive density are added to S1 for adjustment. The specific details are as follows:
[0095] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 90 parts of quartz sand and 6 parts of iron ore powder, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0096] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0097] Embodiment 11
[0098] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Embodiment 9, except that different amounts of compressive density are added to S1 for adjustment. The specific details are as follows:
[0099] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 100 parts of quartz sand and 8 parts of iron minerals, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0100] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0101] Example 12
[0102] This embodiment provides a plugging agent and a preparation method thereof. The preparation steps are the same as those of Embodiment 9, except that different amounts of compressive density adjustment are added to S1, and different amounts of deformation pressure-bearing resin are added to S2. The specific details are as follows:
[0103] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 100 parts of quartz sand and 8 parts of iron minerals, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0104] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 10 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added into S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0105] Comparative Example 1
[0106] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that hydroxypropyl methylcellulose is not added to S1. The specific preparation details are as follows:
[0107] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; after it is uniform, add 90 parts of quartz sand and 6 parts of iron ore powder, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0108] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0109] Comparative Example 2
[0110] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that no gelling particles are added to S1, and the amount of acid-soluble granular calcium carbonate added is different. The specific preparation details are as follows:
[0111] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 97 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 90 parts of quartz sand and 6 parts of iron ore powder, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0112] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0113] Comparative Example 3
[0114] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that acid-soluble granular calcium carbonate is not added to S1, and the amount of gelling particles added is different. The specific preparation details are as follows:
[0115] S1: Preparation of strong retention acid-soluble pressure-bearing gel: weigh 75 parts of G-grade oil well cement, 27 parts of sulphoaluminate cement, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 90 parts of quartz sand and 6 parts of iron ore powder, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0116] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0117] Comparative Example 4
[0118] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that no composite coagulant is added to S1. The specific preparation details are as follows:
[0119] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 90 parts of quartz sand and 6 parts of iron ore powder, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0120] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0121] Comparative Example 5
[0122] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that no compressive density regulator is added to S1. The specific preparation details are as follows:
[0123] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0124] S2: Preparation of deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 3 parts of basalt fiber and 8 parts of glycerol ether-modified deformation-dependent pressure-bearing epoxy resin (SMEP) were evenly mixed, added to S1, and stirred at the same speed for 10 minutes to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0125] Comparative Example 6
[0126] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that basalt fiber is not added to S2. The specific preparation details are as follows:
[0127] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 90 parts of quartz sand and 6 parts of iron ore powder, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0128] S2: Preparation of deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: 8 parts of glycerol ether-modified deformation-modified pressure-bearing epoxy resin (SMEP) were added to S1 and stirred at the same speed for 10 minutes to obtain a deformation-modified high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0129] Comparative Example 7
[0130] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that no deformation epoxy resin is added to S2. The specific preparation details are as follows:
[0131] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 90 parts of quartz sand and 6 parts of iron ore powder, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0132] S2: Preparation of deformation-induced high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: Add 3 parts of basalt fiber into S1 and stir at the same speed for 10 minutes to obtain a deformation-induced high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0133] Comparative Example 8
[0134] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that quartz sand and iron ore powder are not added to S1, and deformation epoxy resin is not added to S2. The specific preparation details are as follows:
[0135] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate, 5 parts of calcium oxide, and 2 parts of carbon fiber, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, stir at the same speed for 20 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0136] S2: Preparation of deformation-induced high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: Add 3 parts of basalt fiber into S1 and stir at the same speed for 10 minutes to obtain a deformation-induced high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0137] Comparative Example 9
[0138] This comparative example provides a plugging agent and a preparation method thereof. The preparation steps are the same as those in Example 10, except that the fiber reinforcement carbon fiber is not added to S1, and the deformation epoxy resin is not added to S2. The specific preparation details are as follows:
[0139] S1: Preparation of strong retention acid-soluble pressure-bearing gel: Weigh 30 parts of G-grade oil well cement, 10 parts of sulphoaluminate cement, 57 parts of ultrafine calcium carbonate, 18 parts of sodium silicate and 5 parts of calcium oxide, put them into a mixer and mix them evenly, add the evenly stirred mixture into 250 mL of clean water, and stir at 100,000 rpm for 10 min; then add 1.0 part of retention gel hydroxypropyl methylcellulose, and stir at the same speed for 20 min; after being uniform, add 90 parts of quartz sand and 6 parts of iron ore powder, and stir at the same speed for 5 min to obtain a strong retention acid-soluble pressure-bearing gel.
[0140] S2: Preparation of deformation-induced high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs: Add 3 parts of basalt fiber into S1 and stir at the same speed for 10 minutes to obtain a deformation-induced high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
[0141] Test Example 1
[0142] Retention wall test
[0143] (1) After stirring, pour 200 mL of the sample of the embodiment or comparative example to be tested into a paper cup mold. Invert the mold every five minutes and record the time when it does not flow after inversion, which is the retention time on the wall.
[0144] (2) Take the example or comparative example sample that does not flow when inverted within 10 minutes, and immediately pour it into a 2m long flow channel with an inclined angle of 15° after stirring. Observe the time when the sample stops flowing, which is the sample retention time. The shorter the time, the stronger the retention. The test results are shown in Table 1.
[0145] Table 1 Retention and wall hanging performance of embodiments and comparative examples
[0146] Test Case Required duration of stay Example 1 20~25min Example 2 20~25min Example 3 20~25min Example 4 15~20min Example 5 10~15min Example 6 10~15min Example 7 10~15min Example 8 8.6min Example 9 5.3min Example 10 3.2min Embodiment 11 2.5min Example 12 2.5min Comparative Example 1 18h Comparative Example 2 >24h Comparative Example 3 10h Comparative Example 4 15h Comparative Example 5 20~25min Comparative Example 6 5.2min Comparative Example 7 4.6min Comparative Example 8 20~25min Comparative Example 9 15~20min
[0147] The sample of this embodiment has good retention performance and can be quickly retained along the rock surface of the formation cracks, ensuring that the plugging working fluid can stop quickly after reaching the leaking formation.
[0148] Test Example 2
[0149] Sedimentation stability and expansion performance test
[0150] After stirring, pour 15 mL (denoted as V0) of the sample to be tested into a 20 mL measuring cylinder (the inner wall of the measuring cylinder is pre-coated with silicone oil) immediately, and observe the initial stratification time and the stratification volume. The longer the initial stratification time, the more stable the plugging system is, and the smaller the volume of the stratification, the more stable the plugging system is and the less likely it is to settle. Then cover the sample and let it stand at 180°C for 24 hours before demolding. Test the volume after consolidation, denoted as V1, and the expansion rate of the solidified body is calculated according to the following formula:
[0151]
[0152] The obtained test data are shown in Table 2.
[0153] Table 2 Sedimentation stability and expansion performance of examples and comparative examples
[0154]
[0155]
[0156] The embodiments provided by this patent are not easy to delaminate or not delaminate, have good sedimentation stability, and have high-temperature expansion performance. They form bridges after expansion at the bottom of the well to improve the formation sealing ability.
[0157] Test Example 3
[0158] Compressive strength test
[0159] After stirring, the samples of the embodiments or comparative examples to be tested are poured into a standard core mold, placed in a curing device and cured for 24 hours at 180°C, and the cured samples are taken out after cooling. The samples are placed in a pressure testing machine for uniaxial compressive strength testing. The testing instrument is a YAW-300 pressure testing machine produced by Jinan Fangyuan Testing Instrument Co., Ltd. The test data is shown in Table 3.
[0160] Table 3 Uniaxial compressive strength of examples and comparative examples
[0161]
[0162]
[0163] The uniaxial compressive strength of the embodiment provided by this patent reaches or even exceeds the compressive strength of cement, and is suitable for pressure-bearing and leak-proofing in high-temperature wells.
[0164] Test Example 4
[0165] Permeability test
[0166] (1) Acid-dissolved permeability. The samples cured in accordance with Test Example 3 were tested for their original permeability using a high-temperature and high-pressure reservoir damage instrument. After being taken out, the consolidated core body was placed in a 500 mL beaker, 250 mL of 15% hydrochloric acid solution was added, a watch glass was placed, and the core body was placed in a constant temperature water bath at (50±3)°C for 120 min. The core body was taken out from the water bath, and its permeability was tested to obtain the permeability after acid dissolution.
[0167] (2) High-temperature permeability. The core body that has completed the acid-dissolved permeability test is carefully taken out with tweezers, placed in a high-temperature aging tank, placed in a 200°C high-temperature hot rolling furnace and left to stand for 20 days (pay attention to replace the high-temperature hot rolling furnace during this period), and then aired to room temperature and taken out to test its permeability to obtain the high-temperature permeability after aging.
[0168] The main test data of this test case are shown in Table 4.
[0169] Table 4 Reservoir protection performance test of embodiments and comparative examples
[0170]
[0171]
[0172] The embodiment provided by this patent has dense plugging, and the original permeability of the formed plugging layer is low. After acid dissolution, the permeability is significantly increased, and the seepage channel is opened; after high temperature, the bridging material pressure-bearing deformation plugging agent is further degraded, and the permeability of the plugging layer is further improved, ensuring the smooth flow of oil and gas channels, and playing a good reservoir protection effect. Moreover, as time goes by, the pressure-bearing deformation plugging agent is further degraded, and its permeability can increase with time.
[0173] Test Example 5
[0174] Sealing pressure bearing performance
[0175] The metal seam plate with a seam width of 30 mm was immersed in the prepared slurry of the embodiment and comparative example to be tested, cured in a water bath at 60°C for 3 hours, taken out, the outer end surface of the seam plate was cleaned, placed in a curing device, and cured at 180°C or 200°C for 12 hours to obtain a sealed crack plunger. The sealed crack plunger was placed in the holder of the plugging evaluation instrument, and the slurry of the sample to be tested with the same formula was poured in. The confining pressure was set to 25MPa, the outlet was connected to the atmosphere, and the inlet pressure was gradually increased at intervals of 1MPa until the plugging band broke through. The pressure when the plugging band broke and the total filtration loss at the outlet before the plugging band broke were recorded. The results are shown in Table 5.
[0176] Table 5 Plugging pressure bearing performance of examples and comparative examples
[0177]
[0178]
[0179] It can be seen from the table that the plugging agent obtained in Examples 1-11 has high pressure-bearing strength and low leakage. The plugging pressure can reach 28 MPa. Within the plugging pressure range, there is basically no leakage, indicating that the sealed plugging belt that can be formed can effectively prevent the plugging liquid from seeping and leaking.
[0180] In summary, the plugging agent of the present invention, when the cracks open, the deformation pressure-bearing resin can be inserted into the reservoir pores, firmly bridged, and expand after phase change at high temperature, thereby improving the elastic pressure-bearing capacity of the plugging skeleton, and cooperating with temperature-resistant fibers to timely intercept the plugging liquid. The strong retention acid-soluble pressure-bearing gel has the characteristics of strong retention, micro-expansion, and acid-soluble. Under the interception effect of the deformation pressure-bearing resin and the fiber grid, it is quickly retained and accumulated, and efficiently fills the vicious leakage space. Its plugging system can be retained in time within 2.5 minutes. When gradually bearing pressure and plugging under the high temperature and high pressure environment at the bottom of the well, the deformation pressure-bearing resin shows gelling properties and gradually strengthens, and the gelling particles gradually expand and consolidate under the action of the composite coagulant. The combination of the two firmly bonds the plugging materials of different properties of the plugging system, and forms an ultra-low permeability high-pressure plugging body with the well wall, thereby improving the success rate of fracture leakage plugging. The expansion rate of its plugging system can reach more than 30%, and the pressure-bearing capacity of the leaking layer plugging reaches more than 29MPa. During the oil production stage, acid dissolution can be used to block the seepage channels in the formation in the early stage. In the later stage, the deformation pressure-bearing resin will gradually degrade at high temperature, and some residual plugging materials will resume the free flow state, thereby restoring the plugging layer from ultra-low permeability to high permeability and opening the oil and gas channels.
[0181] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0182] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A plugging agent, characterized in that: Calculated by weight, the plugging agent components include: 100-250 parts of water, 150-300 parts of strong retention acid-soluble pressure-bearing gel, 0.5-5 parts of acid-soluble temperature-resistant fiber, and 2-20 parts of degradable deformation pressure-bearing resin.
2. The plugging agent according to claim 1, characterized in that: The strong retention acid-soluble pressure-bearing gel comprises, by weight: 0.5-1.5 parts of retention gel, 35-50 parts of gelling particles, 55-65 parts of acid-soluble particles, 10-25 parts of composite coagulant, 1-5 parts of fiber reinforcing agent, and 60-100 parts of compressive density regulator.
3. The plugging agent according to claim 1 or 2, characterized in that: The retention gel is selected from at least one of hydroxyethyl cellulose, hydroxyethyl methyl cellulose and hydroxypropyl methyl cellulose; and / or The acid-soluble particles include carbonate particles, preferably at least one of calcite, limestone, calcium carbonate and barium carbonate, and have a particle size of 3-15 um; and / or The gelling particles include at least one of G-grade silicate cement or sulphoaluminate cement for oilfield cementing; and / or The composite coagulant is selected from at least one of sodium silicate, calcium oxide, iron oxide or magnesium oxide; and / or The fiber reinforcement is selected from at least one of carbon fiber, high temperature resistant filling fiber PA66, aromatic polyamide fiber, and nano graphite fiber; and / or The compressive density regulator is selected from at least one of iron ore powder, barite and quartz sand.
4. The plugging agent according to any one of claims 1 to 3, characterized in that: The acid-soluble temperature-resistant fiber is selected from at least one of sepiolite fiber and basalt fiber.
5. The plugging agent according to any one of claims 1 to 4, characterized in that: The degradable deformation pressure-bearing resin is selected from at least one of epoxy polymer shape memory resin, carbon fiber reinforced thermosetting resin-based composite material, and styrene-butadiene polymer; Preferably, the degradable deformation-bearing pressure-bearing resin is selected from at least one of glycerol ether-type modified deformation-bearing pressure-bearing epoxy resin SMEP, carbon fiber reinforced thermosetting resin SA-DA, and acrylonitrile-butadiene-styrene ABS type resin PA-737; More preferably, the degradable deformation-bearing pressure-bearing resin is a glycerol ether-type modified deformation-bearing pressure-bearing epoxy resin SMEP.
6. The plugging agent according to any one of claims 1 to 5, characterized in that: The preparation method of the glycerol ether modified deformation pressure-bearing epoxy resin SMEP comprises: A1: Evenly mix the water-based epoxy resin emulsion, the epoxy monomer polypropylene glycol diglycidyl ether, the curing agent diglycolamine and tetravinylpentamine, and heat and cure to obtain a first cured product; A2: Evenly mix the waterborne epoxy resin emulsion, diaminodiphenyl sulfone and tetravinylpentamine, and heat and cure to obtain a second cured product; A3: The first solidified body and the second solidified body are mixed and granulated to obtain a glycerol ether type modified deformation epoxy resin SMEP.
7. The plugging agent according to any one of claims 1 to 6, characterized in that: In the step A1, the mass ratio of the epoxy resin, the epoxy monomer polypropylene glycol diglycidyl ether, diglycolamine and tetraethylene pentamine is 100:(5-15):(20-30):(2-8); preferably, the mass ratio is 100:10:25:5; and / or The curing temperature is 60-100° C. and the curing time is 2-4 hours; and / or In the step A2, the mass ratio of the waterborne epoxy resin, diaminodiphenyl sulfone and tetraethylene pentamine is 100:(50-70):(10-30); preferably, the mass ratio is 100:60:20; and / or The curing temperature is 80-140° C. and the curing time is 2-10 hours; and / or In the step A3, the mass ratio of the first solidified body to the second solidified body is (1-3):1; preferably, the mass ratio is 2:
1.
8. A method for preparing the plugging agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: mixing gelling particles, acid-soluble particles, composite coagulant, fiber reinforcing agent, water, retention gel, and compression density regulator to obtain a strong retention acid-soluble pressure-bearing gel; S2: Evenly mix the strong retention acid-soluble pressure-bearing gel obtained in step S1, the acid-soluble temperature-resistant fiber, and the degradable deformation-dependent pressure-bearing resin to obtain a deformation-dependent high-temperature pressure-bearing plugging agent for leakage in fractured reservoirs.
9. The preparation method according to claim 8, characterized in that: In the step S1, by weight, 35-50 parts of gelling particles, 55-65 parts of acid-soluble particles, 10-25 parts of composite coagulant, 1-5 parts of fiber reinforcement, 0.5-1.5 parts of retention gel, and 60-100 parts of compressive density regulator are used; and / or In the step S2, 0.5-5 parts of acid-soluble temperature-resistant fiber and 2-20 parts of degradable deformation-bearing pressure-bearing resin are used, by weight; and / or The mixing conditions in step S1 and step S2 independently include: a stirring rate of 60000-110000 rpm, and a stirring time of 5-30 min.
10. Use of the plugging agent according to any one of claims 1 to 7 or the plugging agent prepared by the preparation method according to claim 8 or 9 in the field of deep well fractures.
Citation Information
Patent Citations
A high filtration loss and high acid solubility plugging agent for reservoir plugging and its preparation method
CN112210353B
A composite gel sealing agent and its preparation method
CN112442343B
Preparation method and application of degradable gel system for drilling and plugging of deep-water and ultra-deep-water fractured reservoirs
CN114058359B
Oil well reservoir fracture plugging agent, and preparation method and application thereof
CN103160262A
Crack plugging agent for oil-base drilling fluids
CN104232037A